CYP1A1m1 and CYP2C9*2 and *3 polymorphism and risk to develop ARV‐associated hepatotoxicity and its severity. Issue 6 (3rd April 2017) - Singh, HariOm; Lata, Sonam; Nema, Vijay; Samani, Dharmesh; Ghate, Manisha; Gangakhedkar, Raman R.
Abstract : Non‐nucleoside reverse transcriptase inhibitors are metabolized in the liver by cytochrome P450 (CYP) isoenzymes. Variations in the genes encoding these enzymes may influence the activity of corresponding metabolizing enzymes. This study aimed at assessing association of CYP2C9 *2 430C/T, CYP2C9* 31075A/C, and CYP1A1m1 3801T/C polymorphism with risk to develop ARV Antiretroviral‐associated hepatotoxicity and its severity. In this case–control study, genotyping of CYP2C9 *2, CYP2C9*3, and CYP1A1m1 genes was done in 34 HIV‐infected individuals with hepatotoxicity and 131 without hepatotoxicity, and 153 unrelated healthy individuals using PCR‐RFLP. CYP1A1m1 3801CC genotype was likely to be associated with severe ARV‐associated hepatotoxicity (OR = 1.78, p = 0.70). CYP1A1m1 3801CC genotype and combined genotype TC + CC were likely to be associated with development of ARV‐associated hepatotoxicity (OR = 2.57, p = 0.08; OR = 1.42, p = 0.17). CYP1A1m1 3801CC genotype among advanced and intermediate HIV disease stage was likely to be associated with advancement of disease (OR = 2.56, p = 0.77; OR = 2.37, p = 0.45). CYP2C9 *31075AC genotype among alcohol users was likely to be associated with development of ARV‐associated hepatotoxicity (OR = 1.67, p = 0.38). CYP1A1m1 3801TC genotype and combined genotype TC + CC among nevirapine users were likely to be associated with severe ARV‐associated hepatotoxicity (OR = 3.68, p = 0.27; OR = 4.91, p = 0.13). Among those who received nevirapine, presence of CYP1A1m1 3801TC genotype was likely to be associated with increased risk of development of ARV‐associated hepatotoxicity (OR = 1.50, p = 0.78). CYP1A1m1 3801TC, 3801CC, and CYP2C9*3 1075AC genotypes among combined alcohol + nevirapine users increased the risk of development of ARV‐associated hepatotoxicity (OR = 1.41, p = 0.53; OR = 1.49, p = 0.83; OR = 1.78, p = 0.35). In conclusion, individuals with CYP1A1m1 3801CC and 3801TC genotypes independently and in the presence of alcohol and nevirapine usage is likely to be associated with increased risk of development of ARV‐associated hepatotoxicity, its severity, and advancement of disease. CYP2C9*3 1075AC genotype with combined alcohol and nevirapine usage indicated a risk for development of ARV‐associated hepatotoxicity.